Law for business - Barnes, A. James; Dworkin, Terry Morehead; Richards, Eric L. (Boston : McGraw-Hill/Irwin, 2009)
Offers a treatment of the legal issues of importance to business students and the business profession. This book uses such techniques as content summaries to apply concepts to practice.
Law, legal reasoning, and the legal profession -- Dispute settlement -- Business ethics and corporate social responsibility -- Business and the Constitution -- Crimes -- Intentional torts -- Negligence and strict liability -- Licensing and intellectual property -- The nature and origins of contracts -- Creating a contract: offers -- Creating a contract: acceptances -- Consideration -- Capacity to contract -- Voluntary consent -- Illegality -- The form and meaning of contracts -- Third parties' contract rights -- Performance and remedies -- Formation and terms of sales contracts -- Warranties and product liability -- Performance of sales contracts -- Remedies for breach of sales contracts -- The agency relationship-creation, duties, and termination -- Liability of principals and agents to third parties -- Employment laws -- Which form of business organization? -- Partnerships -- Formation and termination of corporations -- Management of the corporate business -- Financing the corporation and the role of the shareholders -- Securities regulation -- Legal liability of accountants -- Personal property and bailments -- Real property -- Landlord and tenant -- Estates and trusts -- Insurance -- Negotiable instruments -- Negotiation and holder in due course -- Liability of parties -- Checks and electronic fund transfers -- Introduction to security -- Security interests in personal property -- Bankruptcy -- The antitrust laws -- Consumer protection laws -- Environmental regulation.
Includes index.
Keywords: Commercial law -- United States; Trade regulation -- United States; Business law -- United States